Time to Achieve Full Enteral Feeding in Very Low Birth Weight Infants and Associated Factors in Neonatology Unit, Sanglah Central General Hospital Bali - Made Sukmawati; Kartika Eda Clearesta; I Made Kardana; I Wayan Dharma Artana; Putu Junara Putra; Putu Mas Vina Paramitha Cempaka (Babali Health, 2023)
Background: Intolerance of enteral feeding in premature infants is associated with several morbidities, especially in very low birth weight (VLBW). There were only scarce dietary practices to provide better outcomes in VLBW infants. This study aimed to assess the factors which associated with the time to achieve full enteral feeding (FEF) in VLBW infants. Methods: This was a retrospective study on VLBW infants in Neonatology Unit, Sanglah Central General Hospital, Bali from November 2020 to January 2022. The infants started the trophic feeding with breastmilk and or formula milk. The age of FEF was determined when the target of 150 ml/kgBW/day achieved. The association of risk factors were analyzed using Mann Whitney test, Kruskal-Wallis test, and linear regression analysis. Results: A total subjects of 79 VLBW infants with the median of gestational age 30 weeks (25-38) were recruited. The median age of FEF was achieved in 9(7-15) days. Late trophic feeding (more than 24 hours), severe asphyxia, culture positive-sepsis, using of mechanical ventilator were associated with longer timing of FEF. While in multivariate analysis, small for gestational age (SGA), late trophic feeding, severe asphyxia, absence of prenatal dexamethasone, and culture-positive sepsis were the independent factors of longer FEF in this population. Conclusion: In VLBW  infants, the age of FEF in our population was reached in 2 weeks. Small for Gestational age, late trophic feeding, severe asphyxia, prenatal dexamethasone coverage, and culture-positive sepsis were associated with delay of FEF. Further studies multi-centers and analyzing the factors of delayed TF might needed.